OFDM 기반 WAVE 시스템 동기알고리즘 제안 - 오세갑; 유기희; 강희조; Oh, Se-Kab; Ryu, Ki-Hee; Kang, Heau-Jo (한국항행학회논문지, 2008)
In this paper the Coefficient Tracking Synchronization Algorithm is proposed for the compensation and the suitability of the fast channel fluctuation OFDM in the WAVE(Wireless Access in Vehicular Environments) system. The in progress of standardization WAVE process, IEEE802.11p's physical layer is considered on the coexistence of fading and Frequency offset of OFDM channel to find the system performance ability and the comparing examination which is taken on the proposed method of Coefficient Tracking Synchronization Algorithm and the performance efficiency. Through the simulation result we also can see that the proposed system improves the channel estimation ability and offers an extra efficiency if compared to the existing method. 본 논문에서는 고속의 무선 채널환경에 있는 WAVE시스템에 적합한 계수추적 동기알고리즘을 제안한다. WAVE 시스템에 대한 표준화 작업이 진행 중인 IEEE802.11p의 물리계충인 OFDM 시스템에 대하여 페이딩과 주파수 옵셋이 존재하는 환경을 고려하여 시스템의 성능을 구해내고, 제안하는 계수추적동기 알고리즘을 적용하여 기존 방식과 성능 비교한다. 시뮬레이션을 통해 제안하는 시스템이 기존방식에 비해 우수한 성능을 나타냄을 보인다.